2015
DOI: 10.1007/s10552-015-0569-5
|View full text |Cite|
|
Sign up to set email alerts
|

Explaining variation across grantees in breast and cervical cancer screening proportions in the NBCCEDP

Abstract: Purpose There is substantial variation across the National Breast and Cervical Cancer Early Detection Program (NBCCEDP) grantees in terms of the proportion of the eligible population served by the grantees each year (hereafter referred to as the screening proportion). In this paper, we assess program- and state-level factors to better understand the reason for this variation in breast and cervical cancer screening proportions across the NBCCEDP grantees. Methods We constructed a longitudinal data set, consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 8 publications
2
8
0
Order By: Relevance
“…Subramanian et al [12] examined the factors associated with this variability and identified several program and state-level characteristics as important. A larger number of eligible women, a higher average cost of screening (which includes the cost of screening and diagnostic evaluation and cost of program operations), and a greater proportion of women in urban areas all were associated with a lower proportion of eligible women being screened.…”
Section: The Limits To What Increased Program Efficiency Can Achievementioning
confidence: 99%
“…Subramanian et al [12] examined the factors associated with this variability and identified several program and state-level characteristics as important. A larger number of eligible women, a higher average cost of screening (which includes the cost of screening and diagnostic evaluation and cost of program operations), and a greater proportion of women in urban areas all were associated with a lower proportion of eligible women being screened.…”
Section: The Limits To What Increased Program Efficiency Can Achievementioning
confidence: 99%
“…These articles examine the proportions of women who are eligible for the NBCCEDP and who have been screened for breast and cervical cancer, as well as trends in these proportions during 1997–2012 [3, 4]. Subramanian et al [5] examine program and state-level factors in an effort to better understand reasons for state variation in the proportion of eligible women screened by the NBCCEDP. Dalzell and colleagues provide an in-depth description of the methods and data sets used to generate estimates of the number of women eligible for screening in the NBCCEDP [6].…”
mentioning
confidence: 99%
“…Subramanian et al conducted a study to identify factors associated with variation in screening practices across NBCCEDP grantees and found that the size of the eligible patient population, cost of service delivery, and urban versus rural mix of patients all impacted practice. 18 Upon identifying extensive variation in HPV co-testing uptake among the Connecticut contractors, it may be important to explore the organizational and systems-level factors that could be contributing to these contractor-level differences. While Connecticut is a relatively small state, each contractor does have unique characteristics, including population served and available resources in the local community.…”
Section: Discussionmentioning
confidence: 99%